Resolution of donor non‐alcoholic fatty liver disease following liver transplantation. Issue 9 (13th July 2017) - Posner, Andrew D.; Sultan, Samuel T.; Zaghloul, Norann A.; Twaddell, William S.; Bruno, David A.; Hanish, Steven I.; Hutson, William R.; Hebert, Laci; Barth, Rolf N.; LaMattina, John C.
Abstract: Introduction: Transplant surgeons conventionally select against livers displaying high degrees (>30%) of macrosteatosis (MaS), out of concern for primary non‐function or severe graft dysfunction. As such, there is relatively limited experience with such livers, and the natural history remains incompletely characterized. We present our experience of transplanted livers with high degrees of MaS and microsteatosis (MiS), with a focus on the histopathologic and clinical outcomes. Methods: Twenty‐nine cases were identified with liver biopsies available from both the donor and the corresponding liver transplant recipient. Donor liver biopsies displayed either MaS or MiS ≥15%, while all recipients received postoperative liver biopsies for cause. Results: The mean donor MaS and MiS were 15.6% (range 0%‐60%) and 41.3% (7.5%‐97.5%), respectively. MaS decreased significantly from donor ( M =15.6%) to recipient postoperative biopsies ( M =0.86%), P <.001. Similarly, MiS decreased significantly from donor biopsies ( M =41.3%) to recipient postoperative biopsies ( M =1.8%), P <.001. At a median of 68 days postoperatively (range 4‐384), full resolution of MaS and MiS was observed in 27 of 29 recipients. Conclusions: High degrees of MaS and MiS in donor livers resolve in recipients following liver transplantation. Further insight into the mechanisms responsible for treating fatty liver diseases could translate into therapeutic targets.